Model Pendidikan Nilai dengan Orientasi Pemberdayaan Peserta Didik - Arito Arito; Farihatul Husniyah; Nur Mufida Ramadhanisnaini (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2022)
The concept of good character was popularized by Thomas Lickona by referring to the concept put forward by Aristotle as follows